Functional exercise capacity evaluated by timed walk tests in myasthenia gravis. Issue 2 (17th October 2018) - Salci, Yeliz; Karanfil, Ecem; Balkan, Ayla Fil; Kütükçü, Ebru Çalik; Ceren, Ali Naim; Ayvat, Fatma; Bekircan‐Kurt, Can Ebru; Armutlu, Kadriye
ABSTRACT: Introduction : We sought to evaluate the test–retest reliability and construct validity of the 6‐ and 2‐minute walk tests (6mWT and 2mWT, respectively) in patients with myasthenia gravis (MG). Methods : Thirty‐one patients with generalized MG were enrolled in this study. The 6mWT, 2mWT, MG‐specific quality of life questionnaire Turkish version (MG‐QoL15T), quantitative myasthenia gravis test (QMG), and pulmonary function tests were administered. Results : The intraclass correlation coefficients of 2mWT and 6mWT were 0.894 and 0.932, respectively. The 6mWT and 2mWT had moderate correlations with forced vital capacity, maximal inspiratory pressure, QMG score, and MG‐QoL15T score (ρ for 6mWT: 0.579, 0.539, −0.572, and −0.474; ρ for 2mWT: 0.460, 0.446, −0.532, −0.457). Both tests had similar performances for predicting disease severity (area under the curve = 0.761 for 6mWT and 0.759 for 2mWT). Discussion : The 6mWT and 2mWT have excellent test–retest reliability as well as moderate construct validity for the evaluation of functional exercise capacity patients with MG. Muscle Nerve 59 :208–212, 2019